THE USE OF POINT COUNTERPOINT METHOD TO IMPROVE STUDENTS’ SPEAKING ABILITY - Maharida, Maharida (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
The objective of this research was intended to find out how the Point Counterpoint Method can improve of students’ speaking ability at XI MM I of SMK Negeri 1 Bungoro, Pangkep. The research method used a classroom action research which consisted of two cycles. Each cycle consisted of four meetings. It meant that there were eight meetings for two cycles. This classroom action research was conducted at class XI MM I of SMKN 1 Bungoro, Pangkep on 2012/2013 academic year. The subjects of the research were the students of class XI which consisted of 30 students. The instrument used speaking test. The findings of the research were the improving of the students’ pronunciation, grammar and vocabulary in speaking. The mean score of the students’ pronunciation (vowels and consonant) in D-Test was 42.06, in cycle I was 60.11 and in cycle II was 71.37 and the improvement of the students’ pronunciation mean score in D-Test to cycle I was 43.22%, in cycle I to cycle II was 23.51%, in D- Test to cycle II was 70.07%, while students’ grammar mean score (Simple Present Tense  and Future Tense ) in D-Test was 47.77, in cycle I was 59.24 and in cycle II was 73.58  and the improvement of the students’ grammar mean score in D-Test to cycle I was  23.97%, in cycle I to Cycle II was 24.29%, in D-Test to cycle II was 51.16% while students’ vocabulary (noun and verb) mean score in D Test was 53,3, in cycle I was 63.58 and in cycle II was 72.99 and the improvement of students’ vocabulary mean score in D-Test to cycle I was 19.24%, in cycle I to cycle II was 14.9%, in D-Test to cycle II was 37.16%.The students’ activeness toward teaching learning process by using a Point Counterpoint Method was increased. It can be seen from the observation result of the students’ activeness in the classroom from the first meeting at the first cycle until at the last meeting in cycle II always grow up. It could be stated that the research was successful.